Was motiviert zur Eigenvorsorge? Motivationseffekte von Beteiligungsprozessen in der Klimawandelanpassung. - Grothmann, Torsten (My University, 2017)
Diese Literaturstudie fasst den wissenschaftlichen Sachstand zum Einfluss von Beteiligungsprozessen auf die Eigenvorsorge relevanter Akteure in der Klimawandelanpassung und der Naturgefahrenvorsorge zusammen. Die Studie erfolgt aus einer primär umweltpsychologischen Perspektive und analysiert die Wirkzusammenhänge der drei zentralen Komponenten a) Beteiligungsformate, b) psychologische Einflussfaktoren des Vorsorgehandelns und c) Eigenvorsorge. Die Ergebnisse der Studie zeigen, dass in der wissenschaftlichen Literatur systematische Evaluationen zur Wirkung von Beteiligungsformaten auf Eigenvorsorge derzeit fehlen. Insgesamt ließen sich in der Literaturanalyse nur sehr wenige empirisch fundierte Studien zur Wirksamkeit von Beteiligungsmethoden zur Erhöhung der Eigenvorsorge bei den Teilnehmenden finden. Aus Sicht des Autoren unterstreichen daher die Erkenntnisse dieser Analyse die Notwendigkeit vermehrter Wirkungsanalysen von Beteiligungsprozessen zur Klimaanpassung, um im Sinne einer evidenzbasierten Politik den Einsatz von Beteiligungsformaten in der Klimawandelanpassung sinnvoll weiterzuentwickeln.

The present literature study summarizes scientific knowledge on the effects of participatory processes on prevention behaviour of relevant actors in the areas of climate adaptation and natural hazards. The literature study is carried out from a primarily environmental psychological perspective and analyses causal relations of three central components: a) participatory formats, b) psychological determinants of prevention behaviour, and c) prevention behaviour. The results of the study show that there is a lack of systematic evaluations of the effect of participatory formats on prevention behaviour in scientific publications. The current scientific knowledge therefore offers little help to understand the progress to strengthen prevention through participatory forms as required by the German adaptation strategy and the progress report on the strategy. In the context of the scientific situation, three participatory methods or elements appear particularly promising in their influence on prevention behaviour because they are likely to contribute to increasing prevention by influencing several psychological determinants: 1. Collective development of positive visions of a climate-resilient and natural-hazard-safe future at the local level and of ways to achieve it; 2. Joint disaster prevention drills by disaster relief workers (such as fire brigades) and residents of natural hazard areas; 3. Personal reports of persons at participatory events, who have been affected by natural hazards and/or who have already taken prevention measures and with whom the participants can identify. On the whole, very few empirically based studies on the effectiveness of participatory methods to increase prevention behaviour among the participants could be found in the literature analysis. Therefore, the findings of the present analysis underline the necessity of more evaluation studies of participatory processes for climate adaptation in order to develop the use of forms of participation in climate change adaptation in the sense of an evidence-based policy.
Keywords: Umweltschutz; Klima; Wetterschaden; Vorbeugung; Umweltpsychologie; Partizipation; Wirkungsanalyse; Beteiligungsprozess; Klimawandel; Klimaanpassung; Eigenvorsorge